Systemic Impacts of National Civilized Cities on Sustainable Development: A Quasi-Experimental Analysis of Economic and Environmental Outcomes in China - Weixin Yang; Yunpeng Yang; Zhili Chen; Yuxun Gu (Systems)
This paper explores the systemic relationship between urban civilization initiatives and economic prosperity by examining the economic impact of China’s “National Civilized City” (NCC) designation. We begin by synthesizing literature that addresses the complex interactions between urban development and environmental sustainability, emphasizing a systems approach. A theoretical model is developed to capture the dynamic interplay between urban environmental strategies and socio-economic outcomes, framed within the context of the Sustainable Development Goals (SDGs). Employing a quasi-experimental difference-in-differences (DID) method, we analyze data from a panel of Chinese cities (1997–2019) to assess how the NCC title influences economic growth and urban sustainability. Our results indicate a notable 2.88% increase in GDP per capita associated with the designation; however, this effect varies based on the city’s administrative status and geographical location, highlighting the complex and conditional nature of policy impact on economic development. We conclude by offering policy recommendations that promote a holistic approach to urban planning, fostering synergies between environmental conservation and economic growth. These insights contribute to a deeper understanding of sustainable urban development strategies with relevance to both emerging and developed economies.